18KHT01, a Potent Anti-Obesity Polyherbal Formulation - Prakash Raj Pandeya; Prakash Raj Pandeya; Ramakanta Lamichhane; Gopal Lamichhane; Kyung-Hee Lee; Hyeong Kyu Lee; Su-jin Rhee; Hyun-Ju Jung (Frontiers Media S.A., 2021)
Obesity is a life-threatening metabolic disorder necessitating urgent development of safe and effective therapy. Currently, limited such therapeutic measures are available for obesity. The present study was designed to develop a novel, safe and effective herbal therapy for the management of obesity. A polyherbal formulation (18KHT01) was developed by homogeneously mixing a specific proportion of crude Quercus acutissima (acorn jelly powder), Camellia sinensis (dry leaf buds), and Geranium thunbergii (dry aerial part) along with Citrus limon (fruit juice). Synergistic antioxidant, antiadipogenic, and anti-obesity activities were evaluated by in vitro as well as in vivo studies. In vitro experiments revealed strong synergistic antioxidant and anti-adipogenic activities of 18KHT01. Molecular assessment of 18KHT01 showed significant down-regulation of vital adipogenic factors such as PPARγ, C/EBPα, aP2, SREBP-1c, FAS, and LPL. Based on the results of the preliminary toxicity study, 75 and 150 mg/kg, twice daily doses of 18KHT01 were administered to evaluate anti-obesity activity in diet-induced obese (DIO) C57BL/6J mice model. The major obesity-related parameters such as body weight, weight gain, food efficiency ratio, as well as serum lipid profile were significantly reduced by 18KHT01 with potential synergism. Also, the high-fat diet-induced insulin resistance was suggestively alleviated by the formulation, and thus ameliorated fasting blood glucose. Histological evaluation of liver and white adipose tissue revealed that the significant reduction of fat depositions and thus reduction of these tissue weights. Synergy evaluation experiments exhibited that the 18KHT01 offered strong synergism by improving efficacy and reducing the toxicity of its ingredients. Overall results evidenced the 18KHT01 as a safe and potent anti-obesity herbal therapy.